Technical development and future prospects of cooperative terminal guidance based on knowledge graph analysis: a review - Liu, Shuangxi; Lin, Zehuai; Huang, Wei; Yan, Binbin (Journal of Zhejiang University. A. Science, 2025)
Cooperative guidance is a method for achieving combat objectives through information sharing and cooperative effects, and has emerged as a significant research area in the fields of missile guidance and systematic warfare. This study presents a systematic review and analysis of current research on cooperative guidance. First, a bibliometric analysis is conducted on 513 articles using the Scopus database and CiteSpace software to assess keyword clustering, keyword co-occurrence, and keyword burst, and to later visualize the results. Second, fundamental theories of cooperative guidance, including relative motion modeling methods, algebraic graph theory, and multi-agent consensus theory, are summarized. Subsequently, an overview of current cooperative laws and corresponding analysis methods is provided, with categorization based on the cooperative structure and convergence performance. Finally, we summarize current research developments based on five perspectives and propose a developmental framework based on five layers (cyber, physical, decision, information, and system), discussing potential future advancements in cooperative terminal guidance. This framework emphasizes five key areas of research: networked, heterogeneous, integrated, intelligent, and group cooperations, with the goal of offering trends and insights for future work.